Plasma Levels of Fetuin B and Fibrinogen in Chronic Obstructive Pulmonary Disease: A Preliminary Cross-sectional Study - CV Shri Swathini; MVP Chowdary (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Recent exploratory proteomics study reported increased blood levels of Fetuin B (FETUB) in Chronic Obstructive Pulmonary Disease (COPD). Growing body of evidence demonstrates fibrinogen not only as acute phase reactant but also possesses features advocating as biomarker of COPD. Aim: To determine the blood levels of FETUB and fibrinogen independently as well as in combination COPD and among severity of COPD. Materials and Methods: A single-centred cross-sectional study of eight months duration was conducted during May to December 2017. A total of 76 blood samples (38 COPD patients and 38 controls) were recruited. Based on distribution, parametric and non parametric statistical tools were used. Analysis of co-variance and multiple multivariate linear regression models were utilised to assess the influence of clinical data on FETUB. Steel-Dwass-CritchlowFligner method was employed for multiple pairwise comparisons. Receiver Operating Characteristic (ROC) curve were generated to compute cut-off of FETUB, fibrinogen and their combination. Results: The median age of subjects were 57 years with an IQR of 50-66 years for controls whereas 58 years (IQR 50-65 years) for COPD subjects. In comparison to controls, a significant increase in blood levels of both FETUB and fibrinogen in COPD and Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages of COPD was prominent. Among COPD grades, differences of FETUB levels were significant in GOLD I vs II and GOLD IV vs I, II and III whereas fibrinogen levels in GOLD III from GOLD IV. FETUB showed independent correlation with Forced Expiratory Volume (FEV) 1% pred and severity of COPD. A moderate improvement in combined (FETUB+fibrinogen) analysis of control vs COPD was noticed. Conclusion: The present study demonstrates significant increase in blood levels of FETUB in COPD and among the severity of COPD in comparison to fibrinogen. Hence, FETUB can be a more promising probable inflammatory biomarker in COPD.